Prosocial behavior predicts meaning in life during the COVID-19 pandemic: The longitudinal mediating role of perceived social support - He, Yumei; Liu, Qun; Turel, Ofir; He, Qinghua; Zhang, Shuyue (Frontiers in Public Health, 2023)
TThe ongoing COVID-19 pandemic has been an unexpected long-term negative event. Meaning in life has been linked to better psychological adjustment to such events. The current study used longitudinal data collected during the COVID-19 pandemic to see if perceived social support mediates the relationship between six dimensions of prosocial behavior (altruistic, anonymous, public, compliant, emotional, and dire) and meaning in life. A sample of Chinese college students (N = 514) were tracked at three timepoints (T1, T2, and T3) during the COVID-19 outbreak. A cross-lagged panel model (CLPM) was used for mediation analyses. Except for the Public prosocial behavior, the mediation effect was found in all other five dimensions of prosocial behavior. We also found a longitudinal, bidirectional association between perceived social support and meaning in life. The current study contributes to the growing literature on the significance of prosocial behavior in predicting meaning in life.